Advances in hydroscience. - Yen, Ben Chie, 1935- (Academic Press, 1986)
Advances in Hydroscience, Volume 14-1986 covers topics on the frontiers of hydroscience, including urban hydrology, remote sensing, sewer hydraulics, and computational hydraulics. The book presents articles on state-of-the-art theory and practice in sewer hydraulics and the passive microwave remote sensing of soil moisture. An article on the numerical modeling of unsteady open-channel flow is also encompassed. Hydraulic engineers, hydrologists, earth scientists, agricultural engineers, soil scientists, environmental engineers, and urban designers and planners will find the text invaluable.